Universal Concept in Literary Work Through J.M. Synge’s Riders to the Sea - Manugeren, M; ., Hidayati (KnE Social Sciences, 2018)
The research, based on a one-act play Riders to the Sea by Synge, is to find out the universal concept having a focus on suffering, supernaturalism and death as the representative of universality in any literary work. The story is centered on the protagonist, an old woman, Maurya, who has lost all her male family members, all drowned at sea. The sea becomes a hidden enemy never giving a chance for her to live a life of peace. The sense of universality in literature is inclined to the relationships among human spirit, emotion and social beings. Literature goes beyond national boundaries, time barriers, gender difference and even historical grounds. Literature is not bound to tempora spatio, that is without being restricted by time and space. As a reflection of human life, literature touches all the aspects of human life, tending to create universal appeal. Ashcroft in Waseem (2013) states that universalism offers a hegemonic view of existence by which the experiences, values and expectations of a dominant culture are held to be true for all humanity and this could be traced to all literary works. The study was conducted by means of descriptive qualitative method proposed by Cresswell (2013) indicating that such a method makes a focus on description analysis and interpretation of a given phenomenon. The result showed that the three points of discussion: suffering, supernaturalism and death are clearly exposed in the play, inclining to prove the universal concepts in literature. Keywords: suffering, supernaturalism, death